Profitability, Capital Structure, and Investment Decisions on Firm's Value in the Pharmaceutical Sector in Indonesia: Before, During, and Post the COVID-19 Pandemic - Rahmani, Syifa Afifah; Widyarini, Maria; Intanie Dewi, Vera (Profit: Jurnal Adminsitrasi Bisnis, 2026)
ABSTRACT Investors evaluate a firm's valuation and indicate the amount they are prepared to pay should the company be sold. Factors such as profitability, capital structure, and investment decisions can influence this value. This study aims to analyze the impact of profitability (ROE), capital structure (DER), and investment decisions (PER) on the company value (PBV) of pharmaceutical companies listed on the Indonesia Stock Exchange (g) during the periods before (2018-2019), during (2020-2021), and after the COVID-19 pandemic (2022-2023), both individually and collectively. A quantitative descriptive method was employed, utilizing panel data regression analysis with a fixed effect model. The sample comprised data from 4 pharmaceutical companies listed on the IDX, collected quarterly, resulting in 96 data points. The findings indicate that, overall, all three factors significantly impact the value of pharmaceutical companies listed on the IDX during each period of the COVID-19 pandemic. However, only the capital structure (DER) demonstrated a significant influence when analyzed individually. The sampled pharmaceutical companies rely more on debt than equity to finance their operations. This condition implies that these companies still need to optimize their equity management fully and suggests that share prices can negatively impact company value.